2016
DOI: 10.1016/j.ijheatmasstransfer.2016.05.060
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two-phase inlet quality, mass velocity, flow orientation, and heating perimeter on flow boiling in a rectangular channel: Part 1 – Two-phase flow and heat transfer results

Abstract: Lack of understanding of flow boiling behavior in reduced gravity poses a major challenge to the development of future space vehicles utilizing two-phase thermal control systems (TCSs). A cost effective method to investigating the influence of reduced gravity on flow boiling is to perform ground experiments at different orientations relative to Earth gravity. This paper is the first part of a two-part study aimed at exploring flow boiling mechanisms of FC-72 in a rectangular channel heated along one wall or tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 43 publications
0
9
0
2
Order By: Relevance
“…In an effort to complement previous studies conducted as part of the ongoing project between PU-BTPFL and NASA GRC dealing primarily with characterization and prediction of important time-averaged design parameters such as heat transfer coefficient [44][45][46][47], pressure drop [31,[48][49], and CHF [50][51][52][53], the present study will also present and evaluate several flow boiling stability maps commonly found in literature.…”
Section: (2)mentioning
confidence: 99%
“…In an effort to complement previous studies conducted as part of the ongoing project between PU-BTPFL and NASA GRC dealing primarily with characterization and prediction of important time-averaged design parameters such as heat transfer coefficient [44][45][46][47], pressure drop [31,[48][49], and CHF [50][51][52][53], the present study will also present and evaluate several flow boiling stability maps commonly found in literature.…”
Section: (2)mentioning
confidence: 99%
“…Increasing the mass velocity to G = 406.1-409.0 kg/ m 2 s with an inlet quality of x e,in = 0.03 is shown producing interfacial behavior similar to that for the lower mass velocity. are lowest for top-wall heating (h = 180°) due to vapor stratification along the heated wall, while vertical uplow (h = 90°) and vertical downflow (h = 270°) show better performances, a trend shared with heat transfer coefficients and pressure drops in the first part of this study [40]. CHF values for vertical upflow are slightly higher than those for vertical downflow.…”
Section: Two-phase Flow Loop and Operating Conditionsmentioning
confidence: 63%
“…This study is part of a NASA project whose ultimate goal is to develop the Flow Boiling and Condensation Experiment (FBCE) for the International Space Station (ISS). The first part of the study [40] examined flow boiling interfacial behavior, boiling curves, local and average heat transfer coefficients, and pressure drop. This part of the study will be focused entirely on the combined influences of mass velocity, inlet quality, flow orientation, and both single-sided and double-sided heating on flow boiling CHF, and on CHF modeling.…”
Section: Objective Of Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The current study deals with flow boiling and augments prior work dealing with experimental investigation and prediction of key design parameters including heat transfer coefficient [86][87][88][89], pressure drop [53,[90][91], and critical heat flux [92][93][94][95][96][97][98], with development of a mechanistic model for prediction of frequency and amplitude of DWO induced pressure oscillations evident in vertical upflow boiling with finite inlet quality.…”
Section: Objectives Of Studymentioning
confidence: 99%